2013
DOI: 10.1186/1749-8090-8-83
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and culture of smooth muscle cells from human acute type A aortic dissection

Abstract: BackgroundAcute type A aortic dissection (TAAD) is a life-threatening vascular disease. Smooth muscle cells (SMCs) are the main composition of aortic media and dysfunction of SMCs may lead to acute TAAD. The aim of this work was to investigate whether the SMCs of acute TAAD could be isolated and cultured for further research.MethodsTAAD tissues were obtained from acute TAAD patients who underwent emergent surgical treatment. A simple and economical technique of collagenase digestion method was used to isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The presence of smooth muscle a-actin is the most widely used criterion for identification of smooth muscle cells. We found that smooth muscle a-actin expression was strongly positive and cable-like myofilaments filled in our cultured cells, consistent with observations from other investigators (Dufresne and Warocquier-Clérout 2001;Lu et al 2013;Crosas-Molist et al 2015). However, the immunofluorescence of smooth muscle a-actin was negative in rat PAECs which were stained strongly for von Willebrand Factor.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of smooth muscle a-actin is the most widely used criterion for identification of smooth muscle cells. We found that smooth muscle a-actin expression was strongly positive and cable-like myofilaments filled in our cultured cells, consistent with observations from other investigators (Dufresne and Warocquier-Clérout 2001;Lu et al 2013;Crosas-Molist et al 2015). However, the immunofluorescence of smooth muscle a-actin was negative in rat PAECs which were stained strongly for von Willebrand Factor.…”
Section: Discussionsupporting
confidence: 92%
“…Cytotoxicity was assessed on smooth muscle cells isolated from rat aorta as described in [ 76 ] using the crystal violet assay [ 77 ]. The cells were seeded into 96-well cell culture plates (Greiner, Pleidelsheim, Germany) at a density of 3000 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…SMT quality and any degradation after lyophilization were monitored using 7% SDS/PAGE [ 25 ]. Cytotoxicity was evaluated with smooth muscle cells isolated from bovine aorta as described in [ 29 ] using crystalline violet assay [ 30 ]. The cells were seeded into 96-well cell culture plates (Greiner) at density of 3000 cells per well.…”
Section: Methodsmentioning
confidence: 99%